Present and future habitat suitability of an endemic tree frog, Zhangixalus jarujini, under climate change scenario - CHANTIP CHUAYNKERN; NUTTAPONG KHAJITMATHEE; RATCHATA PHOCHAYAVANICH; WASSANA MAIPHROM; EKACHAI PHETCHARAT; AINGORN CHAIYES; PRATEEP DUENGKAE; YODCHAIY CHUAYNKERN (Society for Indonesian Biodiversity, 2025)
Abstract. Chuaynkern C, Khajitmathee N, Phochayavanich R, Maiphrom W, Phetcharat E, Chaiyes A, Duengkae P, Chuaynkern Y. 2025. Present and future habitat suitability of an endemic tree frog, Zhangixalus jarujini, under climate change scenario. Biodiversitas 26: 4445-4456. Zhangixalus jarujini, a tree frog in the family Rhacophoridae and endemic to northeastern Thailand, is increasingly threatened by habitat degradation and the impacts of climate change. This study utilized ecological niche modeling with the Maximum Entropy (MaxEnt) algorithm to evaluate the species’ current and future habitat suitability across Thailand, Laos, and Cambodia. A total of 16 confirmed occurrence records and 14 environmental variables were used to generate highly accurate models (mean AUC: 0.991±0.001). The most influential predictor variables were distance to water bodies (25.7%), precipitation seasonality (Bio15: 24.5%), precipitation of the warmest quarter (Bio18: 15.0%), normalized difference water index (NDWI: 13.3%), precipitation of the driest month (Bio14: 10.8%), and isothermality (Bio3: 9.2%). Under current conditions, the total area of suitable habitat was estimated at 9,964.58 km², comprising 5,837.82 km² of low suitability, 3,393.10 km² of medium suitability, and 733.67 km² of high suitability. Future projections, based on the ACCESS-CM2 climate model, were conducted under two Shared Socioeconomic Pathways: SSP2-4.5 and SSP5-8.5. By 2050, suitable habitat is projected to expand to 12,178.84 km² (22.22%) under SSP2-4.5 and 12,451.58 km² (24.96%) under SSP5-8.5. By 2070, it may reach 12,113.35 km² (21.56%) and 12,559.14 km² (26.44%) under the respective scenarios. High suitability areas are predicted to increase significantly, with a maximum of 1,228.58 km² under SSP5-8.5 by 2070, representing a 67.46% gain. The most influential environmental variables shaping habitat suitability were distance to water bodies, precipitation seasonality, and precipitation during the driest month. While these projections indicate a potential expansion of suitable habitat, actual population persistence may be constrained by ecological limitations, habitat fragmentation, and human pressures. Based on the model outputs and the availability of similar habitats in adjacent regions, this study strongly recommends systematic and intensive field surveys in Thailand, southern Laos, and northern Cambodia to identify potential undocumented populations and refine conservation priorities for Z. jarujini.